Detrital zircon ages from the Ross Supergroup, north Victoria Land, Antarctica: Implications for the tectonostratigraphic evolution of the Pacific-Gondwana margin - Paulsen, Timothy S.; Deering, Chad D.; Sliwinski, Jakub; id_orcid:0 000-0003-3069-9978; Bachmann, Olivier; Guillong, Marcel (Gondwana Research, 2016)
ISSN:1342-937X ISSN:1878-0571